Project Report On Design and Development Of Communication Floswitch Using Virtex-Fpga - ASHWINI M R,KAMALA R and KRITHIKA ANAND (2013)
INTERNAL GUIDE : HAMEEM SHANAVAS I. EXTERNAL GUIDE:JAGANNADHAM V V. USN NO : 1MJ10EC018,1MJ10EC038,1MJ10EC043. CARRIED OUT AT : National Aerospace Laboratories Bangalore-17 ACC N : PR2129
Keywords: On Design and Development Of Communication Floswitch Using Virtex-Fpga